Population And Unemployment On Poverty In North Sumatra Province - Hasanah, Uswatun (Journal of Management, Economic, and Accounting, 2025)
North Sumatra Province is one of the largest provinces in Indonesia, as a province that has a large population density with a small level of employment opportunities is feared to trigger an increase in poverty in the region.  This study was taken from 33 city districts in North Sumatra within 11 years so that the total data used was 1089. This research uses ARDL Panel analysis method and Paired Sample t-tests. The results of ARDL panel analysis show that Nias, Batubara, Tanjung Balai, Tebingtinggi and Padangsidempuan are districts / cities that become leading indicators of poverty eradication efforts in North Sumatra, the leading indicator of poverty eradication control in North Sumatra is through the variable open unemployment rate, but the variable open unemployment rate and population growth still does not provide a stable influence, which is influential in the long term and short term.